2008
DOI: 10.1016/j.jacc.2008.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Initial Assessment of Clinical Impact of a Drug Interaction Between Clopidogrel and Proton Pump Inhibitors

Abstract: 12. Van den Broek KC, Nyklicek I, Van der Voort PH, Alings M, Denollet J. Shocks, personality, and anxiety in patients with an implantable defibrillator. Pacing Clin Electrophysiol 2008;31: 850 -7. 13. Irvine J, Dorian P, Baker B, et al., for the CIDS Investigators. Quality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 2 publications
6
91
0
3
Order By: Relevance
“…16 However, these studies included relatively few patients and had limited ability to adjust for potential confounders.…”
mentioning
confidence: 99%
“…16 However, these studies included relatively few patients and had limited ability to adjust for potential confounders.…”
mentioning
confidence: 99%
“…Given the marked differences in CYP2C19 inhibition between omeprazole and esomeprazole versus lansoprazole and pantoprazole, qualitative differences between the groups would have been expected [74]. Two other smaller analyses also supported the greater risk of cardiac events with patients receiving concurrent proton pump inhibitors but again, whether the additional risk is due to the underlying differences in the populations versus the use of the drug cannot be determined [75,76].…”
Section: Drug Interactions Impeding Cardiovascular Drug Functionmentioning
confidence: 99%
“…This included an analysis of the Clopidogrel for the reduction of events during observation (CREDO) trial that concluded that use of PPI increased the risk of CV events, but that clopidogrel 40 Further studies have included a retrospective cohort by Pezalla in an initial 2008 letter that observed a slight increase in MI rates in those on PPI, even after accounting for significant comorbidity differences. 41 Three subsequent retrospective studies further examined PPIs and found an OR of 1.25-1.51 when taking a PPI, and further analyzed individual usage of PPIs including Pantoprazole, omeprazole, rabeprazole, lansoprazole and esomeprazole, but found that they all increased risk to some degree. [42][43][44] These retrospective studies have a number of limitations, including lack of controlling for risk factors, making it difficult to form valid conclusions from such analyses and to determine if a class effect for the various PPIs exist.…”
Section: Clinical Effects Of Clopidogrel and Proton Pump Inhibitorsmentioning
confidence: 99%